LG = 50 nm T-gated and Fe-doped double quantum well GaN‒HEMT on SiC wafer with graded AlGaN barrier for future power electronics applications - B. Mounika; J. Ajayan; Sandip Bhattacharya; D. Nirmal; Amit Krishna Dwivedi (Journal of Science: Advanced Materials and Devices)
High-performance LG = 50 nm graded double-channel (GDC)-HEMT featuring AlN top barrier, recessed T-gate and graded-AlGaN bottom barrier is designed and investigated. Two quantum wells are formed in the AlN-GaN-graded AlGaN-GaN multilayer structure developed on a SiC substrate and the clear double hump feature of the transconductance (GM), cut-off frequency (fT), and capacitance plots clearly illustrates the double-channel (DC) behavior. The investigations carried out to explore the impact of barrier thickness (both AlN & graded-AlGaN) revealed superior performance with the GM showing two peaks at 181.5 & 488.1 mS/mm, the peak-drive-current (ID_peak) with VGS biased at 3 V is 1.81 A/mm, maximum saturation drain current of 3.08 A/mm (VGS = 3V), and the fT derived from the left- and right-hump are 263.7 GHz & 354.2 GHz, respectively, when both barriers are 6 nm thin, attributable to enhanced 2DEG density due to the coordination of channels because of proximity and lower leakage. It has been noticed that when the bottom barrier is thick, the DC behaviour is less obvious due to insufficient gate access to the lower channel. We investigated the impact of varying the Al % in AlGaN top barrier on the DC/RF performance of GDC-HEMTs, demonstrating enhanced performance with increased Al content, particularly for Al0.35Ga0.65N. By using various metals, this study also investigates how gate engineering affects the electrical characteristics of the GDC-HEMT. The lower ϕm (work function) of the Al-gate led to better DC/RF performance. When the Schottky barrier rises as a result of the conduction band edge being elevated, the performance reduces, and the threshold voltage (Vth) increases. Since it is essential to comprehend the role that source resistance (Rs) & drain resistance (Rd) play in RF design, we have also conducted simulations by varying the source-gate gap (LGS) & drain-gate gap (LGD). Due to low Rs & Rd, it was determined that the GDC-HEMT performed better at the smallest LGS & LGD. The extraordinary performance strongly highlights the immense potential and applicability of the GDC-HEMTs for future broadband power amplifiers.